1999
DOI: 10.1136/bjsm.33.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Energy cost of sport rock climbing in elite performers.

Abstract: could be the result of repeated isometric contractions, particularly from the arm and forearm muscles. (Br J Sports Med 1999;33:14-18) Keywords: rock climbing; performance; oxygen uptake; heart rate; lactate Sport climbing is a discipline of rock climbing which is performed indoors and outdoors. Indoor sport climbing is characterised by gymnastic type movements on walls fitted with artificial hand and foot holds and is an internationally contested event. Outdoor sport climbing requires similar movements wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
132
9
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(158 citation statements)
references
References 13 publications
12
132
9
5
Order By: Relevance
“…It is likely that this is due to the ease of data collection, potential safety issues and, possibly, the assumption that there are no physiological or psychological differences between indoor and outdoor climbing. In more general climbing research, only four other papers have collected data on natural rock (Booth, Marino, Hill, & Gwinn, 1999;Bunting, Little, Tolson, & Jessup, 1986;Bunting, Tolson, Kuhn, Suarez, & Williams, 2000;Williams, Taggart, & Carruthers, 1978). Further research is necessary in this area, as outdoor traditional and sport climbing affords unique opportunities for the study of psychophysiology and climbing performance, including decisions about the objective dangers, route finding and learning on real rock, which are not present indoors (Lewis & Cauthorn, 2002).…”
Section: Outline Of Climbing Psychophysiology Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that this is due to the ease of data collection, potential safety issues and, possibly, the assumption that there are no physiological or psychological differences between indoor and outdoor climbing. In more general climbing research, only four other papers have collected data on natural rock (Booth, Marino, Hill, & Gwinn, 1999;Bunting, Little, Tolson, & Jessup, 1986;Bunting, Tolson, Kuhn, Suarez, & Williams, 2000;Williams, Taggart, & Carruthers, 1978). Further research is necessary in this area, as outdoor traditional and sport climbing affords unique opportunities for the study of psychophysiology and climbing performance, including decisions about the objective dangers, route finding and learning on real rock, which are not present indoors (Lewis & Cauthorn, 2002).…”
Section: Outline Of Climbing Psychophysiology Literaturementioning
confidence: 99%
“…Whilst only five papers (Booth et al, 1999;Bunting et al, 1986Bunting et al, , 2000Hardy & Hutchinson, 2007;Williams et al, 1978) have looked at climbing outside, only Hardy and Hutchinson (2007) have examined climbing psychophysiology. Furthermore, to our knowledge, as yet there has not been any research conducted comparing climbing indoors and outdoors.…”
Section: Summary Of Future Research Directionsmentioning
confidence: 99%
“…Depending on climbing grade, heart rates ranged from 129 beats per minute in Sheel et al [10] studies to 176 beats per minute in Billat et al [1] investigation; the most frequently reported values being about 160 beats per minute [2,7]. During sport climbing climber's weight is supported intermittently for a considerable period of time with a predominance of isometric contraction of the upper limbs muscles.…”
Section: Discussionmentioning
confidence: 99%
“…There has been not much of research done on sport climbing comparing to the other, "traditional" sports. Biomechanical and physiological approaches have focused on finger strength [5], aerobic and anaerobic capacity of sportsmen [2,8,9] and their anthropometric characteristics [6,14].…”
Section: Introductionmentioning
confidence: 99%
“…Booth et al (14) adopted the same strategy when comparing data obtained in laboratory tests with the ones obtained during an easy route of rock sport climbing. Initially, a maximal ergospirometric test with ergometer specific to sport climbing was applied, during which the highest value of O 2 ( O 2 peak-climbing ), of HR (HR peak-climbing ) and of [La] after the test [La peak-climbing ] in elite climbers were measured.…”
Section: Physiological Responses During Sport Climbingmentioning
confidence: 99%